Development of Radiotracers for Imaging of the PD-1/PD-L1 Axis - Fabian Krutzek; Klaus Kopka; Sven Stadlbauer (MDPI AG, 2022)
Immune checkpoint inhibitor (ICI) therapy has emerged as a major treatment option for a variety of cancers. Among the immune checkpoints addressed, the programmed death receptor 1 (PD-1) and its ligand PD-L1 are the key targets for an ICI. PD-L1 has especially been proven to be a reproducible biomarker allowing for therapy decisions and monitoring therapy success. However, the expression of PD-L1 is not only heterogeneous among and within tumor lesions, but the expression is very dynamic and changes over time. Immunohistochemistry, which is the standard diagnostic tool, can only inadequately address these challenges. On the other hand, molecular imaging techniques such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT) provide the advantage of a whole-body scan and therefore fully address the issue of the heterogeneous expression of checkpoints over time. Here, we provide an overview of existing PET, SPECT, and optical imaging (OI) (radio)tracers for the imaging of the upregulation levels of PD-1 and PD-L1. We summarize the preclinical and clinical data of the different molecule classes of radiotracers and discuss their respective advantages and disadvantages. At the end, we show possible future directions for developing new radiotracers for the imaging of PD-1/PD-L1 status in cancer patients.